Leadership Model in Pesantren: Managing Knowledge Sharing through Psychological Climate - Fikri, Muhamad Agung Ali; Pramono, Tias; Nugroho, Yunianto Agung; Novitasari, Dewiana; Asbari, Masduki (IJOSMAS, 2021)
This study aims to examine the effect of charismatic leadership on the psychological safety climate and tacit knowledge sharing. This study also investigates the central role of psychological safety climate as a mediating variable between charismatic leadership and tacit knowledge sharing. This study adopted a simple random sampling method with 61 samples of ustadz/ustadzah from a Pesantren in Banten. The results of this study indicate that charismatic leadership has a significant direct influence on the climate of psychological security and tacit knowledge sharing. Likewise, the psychological safety climate has a significant direct influence on tacit knowledge sharing. This study also finds evidence that charismatic leadership has a significant indirect effect on tacit knowledge sharing through the mediation of a psychological safety climate. Thus, the psychological safety climate acts as a partial mediator in this research model.